If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 74 + -6 + -1t = 25 Combine like terms: 74 + -6 = 68 68 + -1t = 25 Solving 68 + -1t = 25 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-68' to each side of the equation. 68 + -68 + -1t = 25 + -68 Combine like terms: 68 + -68 = 0 0 + -1t = 25 + -68 -1t = 25 + -68 Combine like terms: 25 + -68 = -43 -1t = -43 Divide each side by '-1'. t = 43 Simplifying t = 43
| .1523= | | .0789= | | 2-5/(3x-7)=2 | | t-8-4=31 | | 1.571428n=44 | | X=-16x^2+80x+0 | | 5y-19=2y+8 | | log(5x)-38=-28 | | 4b-6=6b | | -8(x-5)+2=-7x+7 | | 9x=(27/9)*6 | | 7(x+5)=8x+6 | | (23-3y)/(y-6) | | 9y-2=38+y | | 13x-(3x+12)-12x=-5x+3 | | -2(-3-x)=7 | | 2/3=x/25-x | | 13=2w+3(w+6) | | 6x+4=-28-2x | | -7v+5(v-3)=-23 | | 3x+19=3x-103 | | 12-t+25=23 | | 4*9-5y=26 | | G-5.2=-18.73 | | 4x-5(2)=26 | | 9-17+4x-x=0 | | 3(4x-3)-4(3x+8)=7(x-6) | | 12-4=5x-25 | | 75=P+3.75P | | 9+6=54153 | | f(x)=4x-3x^2-5 | | 7x-y/-1 |